The impact of cultural introduction on improving students’ cross-cultural communication skills in college English teaching - Li, Haibo (Transactions on Economics, Business and Management Research, 2024)
College English teaching is an important component of general higher education in China, with the main task of cultivating students’ comprehensive English application abilities. In English teaching in universities, cultural introduction is an important means of cultivating students’ cross-cultural communication abilities. Implementing cultural introduction in language teaching is of great help in cultivating students’ cross-cultural communication abilities. In English teaching, teachers can use multimedia technology and network resources to teach and introduce excellent traditional Chinese culture, intangible cultural heritage, etc. into the classroom. At the same time, teachers can also cultivate cross-cultural communication skills by introducing Western countries’ festivals, customs, and habits to students. Implementing cultural introduction in college English teaching can not only improve students’ language proficiency, but also increase their understanding and recognition of English speaking countries.